2010
DOI: 10.1111/j.1755-6724.2010.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Mantispid‐Like Species of Rhachiberothinae (Neuroptera: Berothidae) from Baltic Amber, with a Critical Review of the Fossil Record of the Subfamily

Abstract: Whalfera wiszniewskii sp. nov. is described from the Late Eocene Baltic amber. The genus Whalfera is considered as the only fossil genus confidently assigned to the Rhachiberothinae. Others previously placed in this subfamily belong to Paraberothinae (except perhaps for Oisea). The Late Eocene/present Rhachiberothinae and the Cretaceous Paraberothinae are considered to be the subfamilies of Berothidae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…All species of the berothid subfamilies Rhachiberothinae and Paraberothinae and at least one species of Mesithoninae have raptorial forelegs. The Mesithoninae occur in the Late Jurassic to Early Cretaceous (Panfilov 1980;Ren & Guo 1996;Makarkin 1999) and the Paraberothinae only in the Cretaceous (see a review of Makarkin & Kupryjanowicz 2010;Petrulevicius et al 2010). The reported fossil record of the Rhachiberothinae is restricted to the Cenozoic (Whalley 1983;Makarkin & Kupryjanowicz 2010).…”
Section: Systematic Position Of Dipteromantispidaementioning
confidence: 99%
“…All species of the berothid subfamilies Rhachiberothinae and Paraberothinae and at least one species of Mesithoninae have raptorial forelegs. The Mesithoninae occur in the Late Jurassic to Early Cretaceous (Panfilov 1980;Ren & Guo 1996;Makarkin 1999) and the Paraberothinae only in the Cretaceous (see a review of Makarkin & Kupryjanowicz 2010;Petrulevicius et al 2010). The reported fossil record of the Rhachiberothinae is restricted to the Cenozoic (Whalley 1983;Makarkin & Kupryjanowicz 2010).…”
Section: Systematic Position Of Dipteromantispidaementioning
confidence: 99%
“…According to the illustration in Nel et al (2005), no spine-like setae can be observed on the inner edge of the foreleg tibia of Chimerhachiberotha acrasarii Nel et al, 2005, so as Whalfera wiszniewskii Makarkin and Kupryjanowicz, 2010, which, though, was not listed as a Paraberothinae without any reason. Consequently, this character should not be included in the diagnosis for the subfamily.…”
mentioning
confidence: 91%
“…However, as Makarkin and Kupryjanowicz (2010) have shown, there is a large amount of variation of the postocular lobe within Berothidae and even in Mantispidae.…”
mentioning
confidence: 93%
See 2 more Smart Citations